Hypoxaemia in Pertussis - J Gordon Millichap (Pediatric Neurology Briefs)
Breathing movements, airflow and arterial oxygen saturation were recorded in 6 infants aged 3 weeks to 7 months with apneic and cyanotic episodes associated with pertussis and compared with 12 healthy controls at the Dept of Paediatrics, Cardiothoracic Institute, Brompton Hospital, and Communicable Disease Unit, St George’s Hospital Medical School, London.